Effect of pH on Structural, Electrochemical and Photoelectrocatalytic Degradation Properties of Methyl Orange - Zainal, Zulkarnain; Yong Lee, Chong; Zobir Hussein, Mohd; Kassim, Anuar; Azah Yusof, Nor (Asian Journal of Chemistry, 2016)
Photoelectrocatalytic degradation of methyl orange at different pH has been studied using TiO2 thin films. The dye structures in acidic, near neutral and basic media were analyzed using UV-Vis spectrophotometer and FTIR spectrometer. Protonation of azo group altered the dye structure from benzenoid in neutral or alkaline solution to quinoid in acidic medium. Cyclic voltammetry was employed to study the electrochemical characteristics of methyl orange at different pH. It was found that the flat-band potential shifted to more negative potential for the increase of solution pH. The photoelectrocatalytic degradation of methyl orange was found to follow the Langmuir-Hinshelwood pseudo first order kinetic model for all the pH. Solutions at pH 6 exhibited the highest degradation rate followed by pH 3, 9 and 12. The addition of supporting electrolyte increased the photodegradation rate but did not affect the trend. Supporting electrolyte was found to play an essential role in providing the conducting medium and buffering the solution.